Ziarah Wali di Indonesia dalam Perspektif Pilgrime Studies - Masduki, Anwar (Religió: Jurnal Studi Agama-agama, 2015)
Pilgrimage studies is multidisciplinary studies in religious studies involving many perspectives and approaches in the social sciences. Therefore, it cannot be separated from the development of other studies, particularly tourism studies that leads to the current study on religious tourism. This article is a literature review generally tracing the development of theoretical tendencies of the pilgrimage studies. Based on an understanding of some theoretical tendencies, this article attempts to look at and examine the emerging trends in the study of saint’s pilgrimage in Indonesia, as one of the variants in pilgrimage studies. The study attempts to scrutiny (1) the dominant theories of the pilgrimage studies, (2) the study of saint’s pilgrimage in Indonesia, continued with (3) what aspects relate to the study of saint’s pilgrimage, and (4) which are the focus of discussions that still need to be discussed and explored relating to the study of saint’s pilgrimage in Indonesia. The results show that the pilgrimage studies experience recent theoretical developments and trends that emphasize postmodern reasoning, which makes pilgrimage studies vary with a great influence on the study of pilgrimage to the tourism studies.